Corsarism, Commerce and Navigation in the XVth Century: Castile and the Mercantile Galleys of Florence - González Arévalo, Raúl (En la España Medieval, 2011)
Florence developed a system of state galleys in the 15th century. The present article analyzes its role in the Crown of Castile, through the Sea Consul’s orders as well as in private documentation. It studies aspects as diverse as the insertion of Castilian ports into Florentine navigational lines, corsair incidents, freight charges envisaged and news about mercantile practices. There emerges a previously unknown image of the role of Tuscan galleys in the external commercial organization of the Crown of Castile.